PRAGMATIC REPRESENTATION OF JAVANESE CULTURAL VALUES IN SURAKARTA MAYORAL CAMPAIGN BILLBOARDS - Purnomo, Budi (Language Horizon: Journal of Language Studies, 2025)
ABSTRACT. This study examines how Javanese cultural values are pragmatically represented in political campaign billboards during the 2025–2030 Surakarta mayoral election. The study focuses on the campaign discourse of two candidate pairs, Respati Ardi–Astrid Widayani and Teguh Prakosa–Bambang Gage, and examines how language is strategically employed to persuade voters while adhering to locally rooted norms of politeness and social harmony. Using a qualitative descriptive approach, 200 billboard texts were analyzed through the framework of speech act theory and politeness principles. The analysis identifies locutionary, illocutionary, and perlocutionary acts and relates them to Javanese sociocultural concepts such as unggah-ungguh (speech etiquette), andhap asor (humility), rukun (social harmony), and tepa selira (empathic consideration). The findings indicate that directive and expressive speech acts dominate the discourse, functioning not only to mobilize political support but also to construct moral legitimacy and communal alignment. Positive politeness strategies are consistently employed to soften political authority, minimize social distance, and resonate with the cultural expectations of Surakarta’s predominantly Javanese electorate. By foregrounding local wisdom in political messaging, this study contributes to applied linguistics and pragmatics by demonstrating how culturally embedded pragmatic competence shapes persuasive communication in local democratic contexts. Pedagogically, the findings offer valuable insights for integrating local cultural norms into the teaching of pragmatic awareness in political and professional communication. Keywords: Javanese cultural values; political billboard discourse; pragmatic competence; politeness strategies; speech acts